The K to 12 Senior High School Technica-Vocational Livelihood Track is Not at All Ready for Implementation - Caballero, Florencio R.; Cabahug, Ruth G. (JPAIR Institutional Research, 2015)
The K to 12 program in the Philippines was enacted into law on May 15, 2013, through Republic Act 10533, otherwise known as the Enhanced Basic Education Act of 2013. The effort is an act of legislation, putting in place the K to 12 Curriculum, so that the Philippine Basic Education becomes competitive at par with other countries. The Senior High School program is believed to be one of the answers to the country’s issue on the educational system. The study determined the optimal readiness of the three groups of stakeholders, namely: Division of Zamboanga del Sur, Industries, and Community in the implementation of Technical-Vocational Livelihood Track for Senior High School in 2016. The study employed descriptive research design; and used validated survey questionnaires. Results revealed that: 1) in terms of facilities/equipment, the school administrators admitted that they are “not at all ready” in the SHS Technical-Vocational Livelihood Track; and 2) the LGUs and industries are “partially ready” to support the SHS implementation. The study concludes that the K to 12 SHS program is not at all ready for implementation in Zamboanga del Sur. It is recommended that a thorough assessment on the functionalities of facilities and equipment needed for each sub-strand of the TVL Home Economics strand be provided by concerned stakeholders prior to implementation to ensure readiness of the school to offer such strand by academic year 2016. This is also to ensure that development of the required skills among the SHS students will not be sacrificed.